Drug-eluting or bare-metal stents for percutaneous coronary intervention: a systematic review and individual patient data meta-analysis of randomised clinical trials. Issue 10190 (22nd June 2019) - Piccolo, Raffaele; Bonaa, Kaare H; Efthimiou, Orestis; Varenne, Olivier; Baldo, Andrea; Urban, Philip; Kaiser, Christoph; Remkes, Wouter; Räber, Lorenz; de Belder, Adam; van 't Hof, Arnoud W J; Stankovic, Goran; et al.
Summary: Background: New-generation drug-eluting stents (DES) have mostly been investigated in head-to-head non-inferiority trials against early-generation DES and have typically shown similar efficacy and superior safety. How the safety profile of new-generation DES compares with that of bare-metal stents (BMS) is less clear. Methods: We did an individual patient data meta-analysis of randomised clinical trials to compare outcomes after implantation of new-generation DES or BMS among patients undergoing percutaneous coronary intervention. The primary outcome was the composite of cardiac death or myocardial infarction. Data were pooled in a one-stage random-effects meta-analysis and examined at maximum follow-up and a 1-year landmark. Risk estimates are reported as hazard ratios (HRs) with 95% CIs. This study is registered in PROSPERO, number CRD42017060520. Findings: We obtained individual data for 26 616 patients in 20 randomised trials. Mean follow-up was 3·2 (SD 1·8) years. The risk of the primary outcome was reduced in DES recipients compared with BMS recipients (HR 0·84, 95% CI 0·78–0·90, p<0·001) owing to a reduced risk of myocardial infarction (0·79, 0·71–0·88, p<0·001) and a possible slight but non-significant cardiac mortality benefit (0·89, 0·78–1·01, p=0·075). All-cause death was unaffected (HR with DES 0·96, 95% CI 0·88–1·05, p=0·358), but risk was lowered for definite stent thrombosis (0·63, 0·50–0·80, p<0·001) and target-vessel revascularisation (0·55, 0·50–0·60, p<0·001). We saw a time-dependent treatment effect, with DES being associated with lower risk of the primary outcome than BMS up to 1 year after placement. While the effect was maintained in the longer term, there was no further divergence from BMS after 1 year. Interpretation: The performance of new-generation DES in the first year after implantation means that BMS should no longer be considered the gold standard for safety. Further development of DES technology should target improvements in clinical outcomes beyond 1 year. Funding: Bern University Hospital.